Time Varying Stock Market Integration and Diversification Opportunities within Emerging and Frontier Markets - Salahuddin, Sultan; Kashif, Muhammad; Rehman, Mobeen Ur (Public Finance Quarterly, 2020)
This study examines the time-varying feature of Emerging and Frontier stock markets to identify diversification opportunities. For this purpose, we sample 29 emerging and frontier countries ranging from 2000-2018 from America, Europe, Asia, Middle East, and Africa with each region consisting of a panel with one home country and other as remaining countries portfolio. Our results highlight few diversification opportunities in the post-crisis period for international investors in emerging and frontier stock markets as compared to the pre-crisis period. In the post-crisis period; Peru, Philippine, Jordan offer diversification opportunities for long run whereas Brazil, Mexico, Peru in emerging America, Philippine from Emerging Asia, Kazakhstan in frontier Europe, Kenya, Morocco in frontier Africa and Bahrain, Jordan from frontier Middle East offer short-run diversification opportunities for international investors.